Macro-micro relationship in nanostructured functional composites - A. S. Luyt; A. Zanotto; A. Spinella; G. Nasillo; E. Caponetti (eXPRESS Polymer Letters)
This paper examines the results of the characterization of two functional composites: Poly(methyl methacrylate) (PMMA)-Ce:YAG (yttrium aluminium garnet doped with cerium) and PMMA-cobalt hexacyanoferrate (CoHCF). The composites were prepared as possible emitters in the fields of lighting thermal sensors. The prepared composites were characterized using transmission electron microscopy (TEM), nuclear magnetic resonance (NMR) spectroscopy, thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) analyses to study the correlation between micro and macro characteristics. We found that the molecular interactions of the two different fillers with the matrix were localized in different sites of the polymer chains. Moreover, the composites showed an increased thermal strength and stiffness, in particular the PMMA-Ce:YAG composite.